Does Showing Off Help to Make Friends? Experimenting a Sociological Game on Self-Exhibition and Social Networks - Aguiton, Christophe; Cardon, Dominique; Castelain, Aymeric; Fremaux, Pierre; Girard, Hélène; Granjon, Fabien; Nepote, Charles; Smoreda, Zbigniew; Trupia, Dilara; Ziemlicki, Cezary (Proceedings of the International AAAI Conference on Web and Social Media, 2009)
The purpose of this study is to give an empirical glance on different forms of self-exposure on Social Network Sites (SNS). Based on a sociological on-line game, it explores the different tendencies in the self-exhibition shift and tries to find out how it is linked to different strategies in order to choose friends. In the first game, people have to select, among four ranked pictures, the one they would accept to publish on their personal webpage. In the second game, they had to choose friends by discovering, step by step, five informational attributes to their internet profile. Analysis of a sample of 12,354 French respondents shows a middle-range level of exhibition and isolates five different ways to expose oneself: Modest, Traditional Exhibition, Bodily Immodesty, Show-off and Provocative. Those different self-exhibition patterns lead to specific relational behaviors on the Internet. The study underlines socio-demographic differences (age, gender, diploma, and occupation) in self-disclosure practices and shows that exhibition on the Internet must be considered as a strategic performance.